Partial-aperture array imaging in acoustic waveguides. (24th November 2016) - Tsogka, Chrysoula; Mitsoudis, Dimitrios A; Papadimitropoulos, Symeon
Abstract: We consider the problem of imaging extended reflectors in waveguides using partial-aperture array, i.e. an array that does not span the whole depth of the waveguide. For this imaging, we employ a method that back-propagates a weighted modal projection of the usual array response matrix. The challenge in this setup is to correctly define this projection matrix in order to maintain good energy concentration properties for the imaging method, which were obtained previously by Tsogka et al (2013 SIAM J. Imaging Sci. 6 2714–39 ) for the full-aperture case. In this paper we propose a way of achieving this and study the properties of the resulting imaging method.